(untitled) - Garrett, Alfred B. (Waltham, Massachusetts, 1968)
The images on the cover call attention to the relationship between macro observations and the intimate structure of chemical substances and the changes, both chemical and physical, that they undergo.
Keywords: Chemistry,Hóa học